Can rely on guessing blood glucose values in the management of an emergency tooth extraction in diabetic patients. Cross-sectional study in Derna city, Libya - Ashraf Saad Elzer; Hameda Asrafel; Alzubair A Alhasni (African Journal of Advanced Pure and Applied Sciences, 2022)
Aim: The aim of our study was designed to examine how accurate patients with diabetes are at guessing their own blood glucose levels in the context of a routine visit to their normal diabetic clinic. Material and Methods: This is a cross-sectional study conducted at Laboratory of Genetic Engineering Department in College of Medical Technology and Diabetes and Heart Center laboratories in Derna City, Libya over a period of one month from (februey2017 to March 2017). SPSS software was used for data analysis and the appropriate statistical tests were applied at (p value set at 0.05). Results: A total of 104 patients, 57(54.8%) males and 47(45.2%) females were participated in our study with over all mean of age 56.5±9.98 years and over all mean of diabetes duration 12±7.04 yeas. Additionally, when the real blood glucose result was compared to a guessing patient's result using the criterion of (15mg/dl), it was discovered that the majority of our patients underestimated their blood glucose values, with 31/73 (42.5%) falling below the accuracy estimate and 20/73 (27.4%) exceeding it. Additionally, when comparing the real blood glucose result with a guessing patient's result using the criteria of (high, normal, and low), it was discovered that the majority of our patients were able to accurately estimate their blood glucose values 46/87 (52.9%), as opposed to 32/87 (36.8%) with underestimated and 9/87 (10.3%) with overestimated values. Conclusion: Based on the discovery that many people with type 2 diabetes are unable to estimate their blood glucose levels accurately, it is important for general dental practitioners to encourage patient to doing testing of their blood glucose level rather than relying on their perception to estimate their blood glucose level.